Dramaturgical functions of sound accompaniment in Serhii Masloboyshchykov's film "Yasa" - Balabukha, Serhii (Ukrainian Cultural Studies, 2025)
Background. Creative output of Ukrainian director Serhii Masloboyshchikov receives unreasonably limited attention in scholarly discourse. Alongside the broader recognition of his artistic legacy – relevant in Ukraine's ongoing cultural struggle – this article focuses on a distinctive aspect of his cinematographic approach: the construction of dramaturgy through a multilayered sound system. The aim of the study is to identify the dramaturgical functions of each sound layer and to analyze the mechanisms of their interaction with the visual track in Masloboishchikov's recent film Yasa (2024).Methods. The research employs Michel Chion's comparative and shot-breakdown analyses, along with his typology of active listening (reduced, causal, semantic, referential), incorporated by David Sonnenschein in the “sound-sphere” model. Semantic and contextual analytical approaches were also applied.Results. Five sound layers were distinguished in the film:▪ themes performed by the ensemble Hespèrion XXI, functioning as the film's central dramaturgical thread and narrative binder;▪ original music by composers O. Begma and R. Vyshnevskyi, intensifying tension and marking the mystical strand;▪ "Maidan music", grounding the historical context;▪ a Rhodope folk song in the director's individual poetic adaptation, dramatizing the conflict between the two female protagonists;▪ "1st-person p.o.v." sound design that models Darка's traumatic states and encloses the other layers within her subjective experience.The sound component fulfils all four functions identified by Sonnenschein: emotional signifier, continuity filler, narrative cueing, and narrative unifier.Conclusions. "Yasa" demonstrates a complex sound system typical of Masloboi-shchykov's cinema. Sound is treated not as mere accompaniment but as a form-generating element that reveals the film's central themes of war, loss, and trauma. The intricate combination of semantic and referential levels, together with the constant return to subjective sound design, turns the audio into a fully fledged carrier of meaning and an effective instrument for constructing directorial narratives.
Keywords: sound, cinema, music, p.o.v., sound-spheres, active listening, function, Masloboyshchykov, dramaturgy, "Yasa"